Odpowiedź :
x(3x+5)-3x =3x²+5x-3x=3x²+2x
-y(4x+2y)+xy =-4xy-2y²+xy=-4xy+xy-2y²=-3xy-2y²
x(3x-5)-x(2x+5) =3x²-5x-2x²-5x=3x²-2x²-5x-5x=x²-10x
4(2x-3)+x(6x-4)=8x-12+6x²-4x=6x²+8x-4x-12=6x²+4x-12
Odpowiedź:
a) x(3x+5)-3x =
3[tex]x^{2}[/tex]+5x-3x=
3[tex]x^{2}[/tex]+2x
b) -y(4x+2y)+xy=
-4xy-2[tex]y^{2}[/tex]+xy=
-2[tex]y^{2}[/tex]-3xy
c) x(3x-5)-x(2x+5)=
3[tex]x^{2}[/tex]-5x-2[tex]x^{2}[/tex]-5x=
[tex]x^{2}[/tex]-10x
d) 4(2x-3)+x(6x-4)=
8x-12+6[tex]x^{2}[/tex]-4x=
6[tex]x^{2}[/tex]+4x-12=
2(3[tex]x^{2}[/tex]+2x-6)